Invasive Meningococcal Disease in Africa's Meningitis Belt: More Than Just Meningitis?. (31st October 2019) - Reese, Heather E; Ronveaux, Olivier; Mwenda, Jason M; Bita, Andre; Cohen, Adam L; Novak, Ryan T; Fox, LeAnne M; Soeters, Heidi M
Abstract: Since the progressive introduction of the meningococcal serogroup A conjugate vaccine within Africa's meningitis belt beginning in 2010, the burden of meningitis due to Neisseria meningitidis serogroup A (NmA) has substantially decreased. Non-A serogroups C/W/X are now the most prevalent. Surveillance within the belt has historically focused on the clinical syndrome of meningitis, the classic presentation for NmA, and may not adequately capture other presentations of invasive meningococcal disease (IMD). The clinical presentation of infection due to serogroups C/W/X includes nonmeningeal IMD, and there is a higher case-fatality ratio associated with these non-A serogroups; however, data on the nonmeningeal IMD burden within the belt are scarce. Expanding surveillance to capture all cases of IMD, in accordance with the World Health Organization's updated vaccine-preventable disease surveillance standards and in preparation for the anticipated introduction of a multivalent meningococcal conjugate vaccine within Africa's meningitis belt, will enhance meningococcal disease prevention across the belt.